Cross-Regional Differences in News Tone and Local Stock Ownership - Mavruk, Taylan (Management Science, 2021)
This study examines cross-regional differences in news tone for the same news event and relates it to local stock ownership of individual investors using a combination of detailed investor and media data. The results show that news tone amplifies the overall attention effect and decreases the difference between the trading activities of local and nonlocal investors when locally sourced news is republished across regions. In general, trading activity decreases for given republished news, but it still exists because the same news event garners attention as it diffuses to other regional outlets in a different news tone. Overall, individual investors seem to realize that the news is stale but expect subsequent price reversals following the republished news, thus showing news-contrarian trading behavior. Furthermore, they distinguish good firms from bad firms, indicating that adverse selection is partially responsible for the observed news-contrarian trading behaviors. This paper was accepted by David Simchi-Levi, finance.